2008
DOI: 10.1111/j.1525-1438.2007.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16INK4a and cervical infection with high-risk human papillomavirus are not related to p53 activity in cervical intraepithelial neoplasia

Abstract: The objective of the study was to investigate the expression of p53 and p16(INK4a) in cervical intraepithelial neoplasia (CIN) and their relation with disease severity and high-risk human papillomavirus (HR-HPV) status. A series of 125 women with previous positive Pap smear were selected for this cross-sectional study. All patients underwent gynecological examination, including colposcopy. Specimens for Pap smears, Hybrid Capture 2 (HC2) test, and pathologic analysis were obtained. After evaluation of CIN grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The p53 oncoprotein expression has been detected in carcinomas from various sites, including breast, colon, bladder and lung. However, the correlation between HPV and p53 IHC staining in cervical lesions has been controversial (27,28). In the present study, no significant correlation was observed between p53 expression and cervical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 oncoprotein expression has been detected in carcinomas from various sites, including breast, colon, bladder and lung. However, the correlation between HPV and p53 IHC staining in cervical lesions has been controversial (27,28). In the present study, no significant correlation was observed between p53 expression and cervical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several immunohistochemical studies on the expression of p53 in cervical intraepithelial lesions have been recently conducted and commonly report an increased frequency of p53 overexpression in HSIL as compared to LSIL . On the other hand there are also reports, albeit limited in number, suggesting that the levels of p53 overexpression may be higher in low grade lesions as compared to higher grade dysplasia or that there is no correlation whatsoever between p53 expression and intraepithelial disease grade . Significant discrepancies also exist with respect to the reported frequencies of p53 overexpression among LSIL or HSIL cases, respectively, as different studies report widely varied rates.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies have investigated p53 protein expression in cervical intraepithelial lesions and in invasive carcinomas, but some of these results are contradictory . Furthermore, the published data on the expression of PTEN and Fas proteins in cervical intraepithelial neoplasia are rather limited, while, to the best of our knowledge, there are no previous immunocytochemical studies on the expression of these proteins in liquid‐based cervical smears.…”
mentioning
confidence: 95%
“…Many recent studies have found the importance of p16 and p53 in cervical neoplasia 9,[12][13][14][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] . The vast majority rated the immunomarker positivity percentage for the presence of cervical intraepithelial neoplasia and correlated with the lesion severity 9,12,13,17,18,[21][22][23][24][25][26][27][28][29] . However, few studies related immune reaction with disease recurrence and/or prognosis 13.14-31 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…However, studies have failed to demonstrate different scores of p53 immunoreactivity in cervical intraepithelial neoplasia and cervical cancer. Conflicting results have also reported the relationship between p53 expression and progression of cervical intraepithelial neoplasia 12 .…”
Section: Fonseca Fonseca Fonseca Fonseca Fonsecamentioning
confidence: 99%